Squaring the Circle Reconciling the Need for Rigor with the Reality on the Ground in Resilience Impact Assessment - Béné, Christophe; Chowdhury, Fahim S.; Rashid, Mamun; Dhali, Sabbir A.; Jahan, Ferdous (Elsevier, 2017)
Currently shaping a large part of the development and humanitarian agenda the concept of resilience has been embraced by a large number of donors, development agencies, and international NGOs. As a consequence, an increasing number of development interventions that aim at strengthening the resilience of vulnerable households and communities are now being implemented across the globe. Along with these interventions, a growing and urgent call for rigorous monitoring and evaluation has emerged. Unfortunately, the very few resilience measurement frameworks that are available are often too “academics”, data-demanding, and therefore poorly adapted to the reality faced by practitioners on the ground. In this paper we develop a resilience impact assessment framework which addresses this challenge. Using an ex-post treatment vs. control approach, the framework satisfies the requirement for rigor that should be found in any proper impact assessment framework, but remains operational in the data- and resource-constrained situations which characterize most of the current interventions in the field. We illustrate the approach through the case of the Enhancing Resilience program that was implemented by the World Food Programme and its partners in Bangladesh during 2011–13.